Analysis of the Alternative Pathways for the β-Oxidation of Unsaturated Fatty Acids Using Transgenic Plants Synthesizing Polyhydroxyalkanoates in Peroxisomes - Allenbach, Laure (American Society of Plant Physiologists, 2000)
Degradation of fatty acids having cis-double bonds on even-numbered carbons requires the presence of auxiliary enzymes in addition to the enzymes of the core β-oxidation cycle. Two alternative pathways have been described to degrade these fatty acids. One pathway involves the participation of the enzymes 2,4-dienoyl-coenzyme A (CoA) reductase and Δ(3)-Δ(2)-enoyl-CoA isomerase, whereas the second involves the epimerization of R-3-hydroxyacyl-CoA via a 3-hydroxyacyl-CoA epimerase or the action of two stereo-specific enoyl-CoA hydratases. Although degradation of these fatty acids in bacteria and mammalian peroxisomes was shown to involve mainly the reductase-isomerase pathway, previous analysis of the relative activity of the enoyl-CoA hydratase II (also called R-3-hydroxyacyl-CoA hydro-lyase) and 2,4-dienoyl-CoA reductase in plants indicated that degradation occurred mainly through the epimerase pathway. We have examined the implication of both pathways in transgenic Arabidopsis expressing the polyhydroxyalkanoate synthase from Pseudomonas aeruginosa in peroxisomes and producing polyhydroxyalkanoate from the 3-hydroxyacyl-CoA intermediates of the β-oxidation cycle. Analysis of the polyhydroxyalkanoate synthesized in plants grown in media containing cis-10-heptadecenoic or cis-10-pentadecenoic acids revealed a significant contribution of both the reductase-isomerase and epimerase pathways to the degradation of these fatty acids.